If it's not what You are looking for type in the equation solver your own equation and let us solve it.
7x-2(x-6)=3
We simplify the equation to the form, which is simple to understand
7x-2(x-6)=3
Reorder the terms in parentheses
7x+(-2x+12)=3
Remove unnecessary parentheses
+7x-2x+12=+3
We move all terms containing x to the left and all other terms to the right.
+7x-2x=+3-12
We simplify left and right side of the equation.
+5x=-9
We divide both sides of the equation by 5 to get x.
x=-1.8
| 3x+2=5y | | 4(x-5)+11=3(x+2)-3 | | 5(x+0.4)=5 | | 5x+11+119=180 | | 7(2x-1)=3 | | 3+13=2x | | y=5x+11+119 | | -12(3x+5)= | | 2.1x+55.9=10.0-13.2x | | 10x=5(x-11) | | -59-2x=13-10 | | 3n+(1-n)-n=-6 | | 45z-90z= | | 6x[5x-7]=432 | | x+1=44 | | 13-9x=51-2x | | 7a+9b= | | 3(a-2)+5w=22 | | 2x^3+5x^2-12=0 | | -19-9x=10x+23 | | 3m+4-9m=-9-6m+23 | | 16x-8=14x+4 | | 3(3+6x)-3=114 | | 6-68= | | 68-6= | | 5x+2(6x-8)=120 | | 17.92=x-0.2x | | 35e+23-30e=48 | | 4(3x-3)=24 | | 13-6x=3x+24 | | 5z-6=x | | 1+2x=9+3x |